Challenges and responses to the scholarship of teaching and learning paradigm among clinical lecturers - Devaraj, Navin Kumar; Abdul Rashid, Aneesa; Ching, Siew Mooi; Cheong, Ai Theng (Centre for Academic Development (CADe) Canselori Putra Building Universiti Putra Malaysia 43400 UPM Serdang, Selangor, 2019)
The way of how teaching and learning is now conducted is way different from how it was done a decade or two before. Gone are the days where the ‘boring’ one- or two-hours lectures by the earlier generations are welcomed. In this era of generation Y learners, teaching needs to be both ‘enjoyable’ and innovative. This presents a huge challenge for a clinician, who now has to teach in a new role as a clinical lecturer. The clinician has spent most of his/her time in consultation rooms or hospitals treating one to one patient but now rather scarily have to face a room full of knowledge-thirsty and tech-savvy young minds. This scenario also applies to medical students, who acquire digital knowledge at an alarming fast rate. As imprinted in the latest Education blueprint, innovative teaching is being outlined as one of the strategies to enhance the teaching methods in order to improve learning (Ministry of Education Malaysia, 2015; 2017).This is to create a learning environment that is more dynamic and conducive so as to improve the overall quality of teaching and learning through a more practical based knowledge curriculum that will equip the young minds with skills to work in an ever challenging environment. Based on the aforesaid context, a new clinical lecturer faces several challenges. Firstly, the clinician lecturer is in an unfamiliar teaching position. Secondly, they face Gen Y learners with different learning expectation who are extremely comfortable with the use of mobile apps and electronic methods of assessment (Eddy, 2011). Thirdly, they are expected to conduct research and publish in high impact journals while facing the increasing workload as a clinician, lecturer and researcher. Given the aforementioned context as clinical lecturers, this chapter will delve into some common challenges and seek possible solutions that may be employed to enhance SoTL.